Methods in Quaternary Ecology #4. Freshwater Sponges - Harrison, Federick (Geoscience Canada, 1988)
Summary In recent years, there has been an increased awareness of the value of fossilized remains of freshwater sponges in Quaternary paleo-ecological reconstructions. Because the taxonomy and ecology of extant forms have been clarified, and because a well-defined fossil record exists that exhibits continuity with extant species, the stage is set for wide-spread utilization of freshwater sponge remains in Quaternary environmental reconstructions. This paper presents an introduction to the freshwater sponges, techniques for their utilization in Quaternary paleo-ecological studies, and summarizes some of the most recent work performed in North America.